Post-activation Performance Enhancement in the Bench Press Throw: A Systematic Review and Meta-Analysis - Krzysztofik, Michal; Wilk, Michal; Stastny, Petr; Golas, Artur (Frontiers in Physiology, 2021)
Background: The purposes of this meta-analysis were to determine the effects of different types of conditioning activity (CA) on subsequent bench press throw (BPT) performances among resistance-trained males. Objective: The purposes of this meta-analysis were to determine the effect of performing a CA on subsequent bench press throw performances and the influence of different types of CA, intra-complex rest intervals, and intensities during the CA on the upper-body post-activation performance enhancement effect. Methods A search of electronic databases (MEDLINE, PubMed, and SPORTDiscus) was conducted to identify all studies that investigated the post-activation BPT performance enhancement up to August 2020. Results: The effect of post-activation BPT performance enhancement was small (effect size - ES=0.29; p=0.01). The ballistic-plyometric exercise and bench press (BP) exercise performed at an intensity of 65-84% one repetition maximum (1RM) (ES=0.29 and ES=0.28; respectively) induced greater enhancement than the BP exercise at 85%1RM and at >100%1RM as well than the concentric-only BP (ES=0.21; ES=0.22; ES=0.11; respectively). A multiple set (ES=0.29) of the CA resulted in a slightly greater enhancement than a single set (ES=0.28). The moderate rest intervals induced a considerably greater effect for CA at an intensity below 85%1RM (5-7 min., ES=0.38) than a shorter (0.3-4 min., ES=0.28) and longer (8 min., ES=0.15). Considering intensity above 85%1RM during the CA, a moderate rest interval resulted in a slightly greater effect (5-7 min., ES=0.3) than a longer (8 min., ES=0.29), while shorter resulted in a negative effect (0.3-4 min., ES=-0.13). Conclusion: The present meta-analysis shows that performing a CA induces a small PAPE effects for the bench press throw performance in resistance-trained males. Individuals seeking to improve their bench press throw performance should consider preceding them with multiple sets of a ballistic-plyometric exercise at low-intensity (i.e. bench press throw at 30%1RM or bodyweight plyometric push-ups), or the bench press exercise at moderate-intensity (65-84% 1RM), performed 5-7 minutes before the explosive activity. However, due to the considerably fewer equipment requirements, the employment of ballistic-plyometric exercises as a CA may be an easy and equally effective solution to induce upper-body PAPE effect.